A retrospective analysis of the outcomes in visual acuity and keratometry readings after corneal collagen crosslinking in keratoconus - Rowjee, Taruna (My University, 2017)
Purpose: To evaluate if corneal collagen crosslinking carried out on patients with keratoconus, slows down or halts the progression of keratoconus. To determine which group of keratoconus patients benefited most from the procedure. Methods: A retrospective record review of 41 eyes of 29 patients. Visual acuity and keratometry measurements were recorded for the involved eye pre-crosslinking and at 3 months and 6 months post-crosslinking. A comparison of these variables pre-crosslinking and at 6 months post-crosslinking was made to determine if there was a flattening of corneal curvature (keratometry readings) and an improvement in visual acuity. Patients were further divided into 3 groups of keratoconus, based on their keratometry readings (measured in diopters): mild keratoconus (≤47 diopters), moderate keratoconus (48 – 54 diopters) and advanced keratoconus (≥55 diopters), to determine which group of keratoconus had the best keratometry reduction readings. Results: After crosslinking took place on 41 eyes, the UnVA of 16(39%) eyes showed an improvement at 6 months, 17(41%) eyes showed no change and 8(20%) eyes showed a decrease in UnVA at 6 months, compared to pre-CXL values. For BCVA, 12(29%) eyes showed an improvement at 6 months, 18(44%) eyes showed no change and 11(27%) eyes showed a decrease in BCVA at 6 months, compared to pre-CXL values. Keratometry readings however showed that 23(56%) eyes had an average flattening of corneal curvature readings of 0.7 D and the remaining 18(44%) eyes showed more steepening (worsening) of the corneal curvature readings of 0.9 D after 6 months post-CXL. 30(73%) eyes had mild keratoconus, 7(17%) had moderate keratoconus and 4(10%) had advanced keratoconus. 19 of the 30 eyes in the mild keratoconus group (73%) showed an average flattening of corneal curvature of 0.6 D. 4 of the 7 eyes in the moderate keratoconus group (17%) showed an average flattening of corneal curvature of 0.7 D. All 4 patients in the advanced group (10%) had steepening (worsening) of their corneal curvatures with an average of 1.2 D. Conclusion: Corneal collagen crosslinking performed on keratoconus patients at least halts the progress of keratoconus. 6 months after CXL most patients showed minimal change from pre-CXL to 6 months in both visual acuity and keratometry. However a longer follow up period and larger sample size is needed to determine if vision and keratometry readings can improve significantly.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in the fulfillment of the requirements for the degree of Master of Medicine in Ophthalmology. Johannesburg, February 2017
Keywords: Visual Acuity Keratometry Keratoconus Corneal